2015
DOI: 10.1371/journal.ppat.1004653
|View full text |Cite
|
Sign up to set email alerts
|

Phage-mediated Dispersal of Biofilm and Distribution of Bacterial Virulence Genes Is Induced by Quorum Sensing

Abstract: The microbiome and the phage meta-genome within the human gut are influenced by antibiotic treatments. Identifying a novel mechanism, here we demonstrate that bacteria use the universal communication molecule AI-2 to induce virulence genes and transfer them via phage release. High concentrations (i.e. 100 μM) of AI-2 promote dispersal of bacteria from already established biofilms, and is associated with release of phages capable of infecting other bacteria. Enterococcus faecalis V583ΔABC harbours 7 prophages i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 41 publications
(46 reference statements)
2
73
1
Order By: Relevance
“…For example, diverse mobile elements coordinate their dissemination via QS, including AHL-based control of conjugative Ti plasmid transfer in Agrobacterium tumefaciens (Fuqua and Winans, 1994). Furthermore, many QS signals, including AHLs, Pseudomonas quinolone signal (PQS), and AI-2, can induce prophage induction in Gram-positive and Gram-negative bacteria (Fernández-Piñar et al., 2011, Hargreaves et al., 2014, Rossmann et al., 2015). It is salient that we observed QS-dependent regulation of type III-A activity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, diverse mobile elements coordinate their dissemination via QS, including AHL-based control of conjugative Ti plasmid transfer in Agrobacterium tumefaciens (Fuqua and Winans, 1994). Furthermore, many QS signals, including AHLs, Pseudomonas quinolone signal (PQS), and AI-2, can induce prophage induction in Gram-positive and Gram-negative bacteria (Fernández-Piñar et al., 2011, Hargreaves et al., 2014, Rossmann et al., 2015). It is salient that we observed QS-dependent regulation of type III-A activity.…”
Section: Discussionmentioning
confidence: 99%
“…The involved bacteriophage is closely related to the filamentous phage Pf1 and exists as a prophage within the bacterial genome (Webb et al ., ). A biofilm dispersal process linked to prophage induction was also observed in Enterococcus faecalis (Rossmann et al ., ) (Table ). Rossmann et al .…”
Section: Molecular Mechanisms Governing Biofilm Dispersalmentioning
confidence: 97%
“…Rossmann et al showed that the AI-2 universal QS molecule is a strong inducer of prophages in E. faecalis V583DABC. Exogenous addition of AI-2 up-regulates the genes of prophage 5 (pp5) that are involved in lysis (i.e., endolysin, holing) resulting either in a significant reduction in biofilm formation by E. faecalis or in a dispersal of an already formed biofilm (Rossmann et al, 2015). However, the underlying mechanism of dispersal through phage release is still not elucidated.…”
Section: Effectors Promoting Biofilm Dispersalmentioning
confidence: 99%
“…Besides spreading virulence and antibiotic resistance markers among bacteria, bacteriophages can promote the expression of virulence/resistance traits of the infected cell. For instance, a polylysogenic Enterococcus faecalis strain displayed greater virulence than the prophage-free isogenic strain in sepsis and endocarditis animal models [39]. Similarly, temperate phage Pf4 participates in the pathogenicity of its host, P. aeruginosa, as shown in a mouse infection model [40].…”
Section: Virulence and Antibiotic Resistancementioning
confidence: 99%